Gene mutations and clinical prognosis of mucosal melanoma in different locations of head and neck. (2nd January 2022) - Guo, Wei; Yin, Gaofei; Cui, Chuanliang; Kong, Yan; Huang, Zhigang; Chen, Xiaohong
Abstract: Background: Mucosal melanoma is the second most common subtype of melanoma in China and head and neck region is one of the main sites of this disease. Aims/Objectives: Analyzed the phenotypes of C-Kit, NRAS, PDGFRA and BRAF genes in patients with in different locations to explore the characteristics of gene mutations. Material and Methods: 96 patients were included in this study. C-Kit (exons 9, 11, 13, 17 and 18), NRAS (exons 1 and 2), PDGFRA (exons 12, 14 and 18) and BRAF (exons 11 and 15) were analyzed by PCR amplification and Sanger sequencing. Results: 14 (14.58%) patients had C-Kit mutation, 6 (6.25%) had BRAF mutation, 23 (23.96%) had PDGFRA mutation, and 12 (12.50%) had NRAS mutation. The NRAS mutation ( p = 0.037, 95%CI: 1.050–4.572) was an independent factor affecting distant metastasis and was most commonly found in the nasal cavity/paranasal sinuses ( p = .043) while the BRAF mutation was more common in locations other than the nasal cavity/paranasal sinus ( p = .008) and was associated with local recurrence. Conclusions and Significance: Gene phenotypes of mucosal melanoma in different locations has differences. Lesions in the nasal cavity and paranasal sinus should be assessed separately from other parts such as the nasopharynx.